Seasonal performance of finishing heifers - Langemeier, Michael R.; Mintert, J.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the impact of date of feedlot placement on feed conversion, daily gain, and death loss. Results indicated that heifers placed on feed from September to December required more feed per pound of gain, had lower daily gains and higher death loss, and generally exhibited more variation in feeding performance than heifers placed during the rest of the year. Cattle feeders should take these performance variations into account when developing budgets and calculating breakeven sale prices for heifers.
Keywords: Beef; Feeding performance; Seasonality; Heifers